The writing of where : graffiti and the production of writing spaces - Lesh, Charles N. (Syracuse, New York : Syracuse University Press, 2022)
"The Writing of Where examines how graffiti writers in Boston write and rewrite various spaces within and across the city. Drawing on a four-year study with graffiti writers, this book explores how writing communities-particularly those marginalized by local processes of neoliberal space-produce public texts that at once challenge existing discourses of place and produce new, emergent writing spaces organized around alternative social principles"--
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on August 24, 2022).
eBooks on EBSCOhost
Keywords: Graffiti -- Social aspects -- Massachusetts -- Boston; Graffiti artists -- Massachusetts -- Boston -- Social conditions; Street art -- Social aspects -- Massachusetts -- Boston; Graffiti artists; Graffiti -- Aspect social -- Massachusetts -- Boston; Graffiteurs -- Massachusetts -- Boston -- Conditions sociales; Art dans la rue -- Aspect social -- Massachusetts -- Boston; Graffiteurs; graffiti artists; LANGUAGE ARTS & DISCIPLINES / Rhetoric; Graffiti -- Social aspects; Street art -- Social aspects; Massachusetts -- Boston